Le rendement et le butin. Regard écologique sur l'histoire du capitalisme, The Yield and the Booty. An Ecological Perspective on the History of Capitalism - Charbonnier, Pierre (Actuel Marx, 2013)
This article examines the history of globalized capitalism from the perspective of the relations to the environment which it helped to construct. It proposes a definition of globalized capitalism as a form of relation to nature. If philosophy has frequently postulated that modernity is characterized by the dissociation between the natural and the social, the history of the economic take-off of the states of Western Europe throws a singular light on this hypothesis. Combining a reading of Karl Polanyi and Kenneth Pomeranz, it can be argued that the logic of commodity always tends to render invisible the relations to the environment which define capitalism. The temporal and spatial lag between those populations which live the concrete experience of the industrial revolution and the enormous natural resources required for its appearance enable us to understand how it has been possible for the representation of the economy to become so radically dissociated from its natural metabolism.
History; Political Science
Keywords: globalized capitalism; nature and society; political thought